Comparison of carotid artery intima media thickness in preeclamptic patients with healthy normotensive pregnant women - Maliheh Afiat; Ehsan Esmailpour; Lida Jarahi; Leila Pourali; Golnaz Iranmanesh; Navid Daghighi; Parvaneh Layegh (Mashhad University of Medical Sciences, 2017)
Introduction: Preeclampsia is a multisystem disorder with unknown etiology which raises the risk of developing cardiovascular diseases in later life. On the other hand , recent studies have shown that increase in Carotid intima-media thickness (IMT) could be an independent predictor for early detection of atherosclerotic cardiovascular Diseases. According to Endothelial dysfunction as a common pathogenetic mechanism in preeclampsia and atherosclerotic process, we compared the carotid IMT of women with preeclampsia to healthy controls. Methods and Materials: In this cross-sectional study in the years 1394-95, IMT of common carotid artery was measured by ultrasonography in 30 pregnant women who admitted due to preeclampsia , 30 healthy pregnant women and 30 healthy non-pregnant women who were matched for age and gestational age. Then the data were coded and imputed to the software. Statistical analysis was done using SPSS software (version 11.5) and appropriate statistical tests. The level of statistical significance considerate as lower than 0.05. Results: The Mean IMT of carotid arteries was 0.77 ± 0.29 mm in pregnant women with preeclampsia , 0.52± 0.09 mm in healthy normotensive pregnant women and 0.55± 0.07 mm in healthy non-pregnant women with significant statistical difference among three groups.p value:<0.001). Conclusion: The results of this study showed that IMT as an important and independent marker in the early prediction of atherosclerotic cardiovascular disease in women with preeclampsia is significantly higher than the control groups. Considering the association between increased IMT and higher risk of atherosclerotic diseases, we suggest that women with preeclampsia should be assessed for early detection of atherosclerotic cardiovascular diseases  as a high risk group.